2012
DOI: 10.1016/j.febslet.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a naturally inactive isoform of type III antifreeze protein into one that can stop the growth of ice

Abstract: a b s t r a c tType III antifreeze proteins (AFPs) can be sub-divided into three classes of isoforms. SP and QAE2 isoforms can slow, but not stop, the growth of ice crystals by binding to pyramidal ice planes. The other class (QAE1) binds both pyramidal and primary prism planes and is able to halt the growth of ice. Here we describe the conversion of a QAE2 isoform into a fully-active QAE1-like isoform by changing four surface-exposed residues to develop a primary prism plane binding site. Molecular dynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…). A previous study revealed that replacement of these four residues in nfeAFP11 with the corresponding residues of the QAE1 isoform converted the inactive isoform into a fully active AFP (called QAE1‐like AFP) . This study further found that the triple mutant of nfeAFP11 (V9Q/V19L/G20V) also showed significant TH activity .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…). A previous study revealed that replacement of these four residues in nfeAFP11 with the corresponding residues of the QAE1 isoform converted the inactive isoform into a fully active AFP (called QAE1‐like AFP) . This study further found that the triple mutant of nfeAFP11 (V9Q/V19L/G20V) also showed significant TH activity .…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies also reported that this T18‐Hγ1 resonance was observed in the active mutant of nfeAFP11 (V9Q/V19L/G20V), suggesting the presence of a stable H‐bond between T18‐Hγ1 and a water molecule (Fig. C) . However, like wt nfeAFP11 , the inactive nfeAFP8s did not show these resonances (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…While the QAE1 isoform is able to bind both the primary prism and a pyramidal plane of ice, the SP and QAE2 isoforms can only bind pyramidal ice planes [134]. Interestingly, a triple mutant of the inactive QAE2 isoform (V9Q/V19L/G20V) is able to bind to the primary prism ice plane and shows full TH activity, similar to the QAE1 isoform [135]. More recently, NMR experiments with inactive QAE2-like mutants containing the V20G mutation were reported.…”
Section: Marine-derived Afpsmentioning
confidence: 99%
“…Ice crystal controlling activity is affected to a significant extent by solvent exposed amino acid residues that are found along the ice-binding surface. By changing theses residues to match one of the ice crystal planes, inactive antifreeze protein isoforms can be altered to be active [73]. Consequently, solvent exposed residues play a major role in ice crystal interaction.…”
Section: Biochemistrymentioning
confidence: 99%